Review of studies addressing the issue of fighting addiction during adolescence in Türkiye: technology and substance addiction - Kadan, Gül; Aral, Neriman (Journal of Dependence, 2024)
The aim of the research is to examine the studies carried out on substance and technology addiction in Türkiye in recent years, by taking them together. Document analysis technique, one of the qualitative research methods, was used in the research. Research on the practices carried out between January 1st 2010 and March 1st 2023 in the fight against substance and technology addiction in Türkiye was examined. In the research where 76 articles and theses were examined, it was determined that the studies were mostly theses (n = 40), were conducted in 2018 and 2021 (n = 14), and were carried out on an experimental basis (n = 26). As a result of the research, it was determined that the publications examined were mostly conducted abroad to combat substance addiction and cyberbullying addiction, to determine protective and preventive factors, and to determine the effectiveness of the applied psychoeducation program. In the reviewed publications, it was determined that the emphasis was on protective and preventive services at the local level in the fight against addiction, multidisciplinary studies were carried out, and results were reached that the applied trainings were effective in reducing addiction. Based on the findings obtained from the research, suggestions were made that different educational models should be integrated and implemented, experimental and longitudinal studies should be included in the fight against substance addiction, interventions that include the entire environment of the adolescent child should be implemented more, and parents should be supported.